OS, PB, AND ND ISOTOPE GEOCHEMISTRY OF THE PERMIAN EMEISHAN CONTINENTAL FLOOD BASALTS: INSIGHTS INTO THE SOURCE OF A LARGE IGNEOUS PROVINCE - Xu J.-F.; Xu Y.-G.; Mei H.-J.; Li J.; Suzuki K. (My University, 2007)
The nature of the source of continental flood basalts (CFB) is a highly debated topic. Proposed mantle sources for CFBs, including both high- and low-Ti basalts, include subcontinental lithospheric mantle (SCLM), asthenospheric mantle, and deep, plume-related mantle. Re-Os isotope systematics can offer important constraints on the sources of both ocean island basalts (OIB) and CFB, and may be applied to distinguish different possible melt sources. This paper reports the first Re-Os isotope data for the Late Permian Emeishan large igneous province (LIP) in Southwest China. Twenty one CFB samples including both low- and high-Ti basalts from five representative sites within the Emeishan LIP have been analyzed for Os, Nd, and Pb isotopic compositions. The obtained Os data demonstrate that crustal assimilation affected Os isotopic compositions of some Emeishan basalt samples with low Os concentrations but not all of the samples, and the Emeishan basalts with high Os contents likely experienced the least crustal contamination. The low and high-Ti basalts yield distinct Os signatures in terms of 187Os/188Os and Os content. The low-Ti basalt with the highest Os concentration (400 ppt) has a radiogenic Os isotopic composition (γOs(t), +6.5), similar to that of plume-derived OIB. Because the Os isotopic composition of basalts with relatively high Os concentrations (typically >50 ppt) likely represents that of their mantle source, this result implies a plume-derived origin for the low-Ti basalts. On the other hand, the high-Ti basalts with high Os concentration (over 50 ppt) have unradiogenic Os isotopic signatures (γOs(t) values range from -0.8 to -1.4), suggesting that a subcontinental lithosphere mantle (SCLM) component most likely contributed to the generation of these magmas. Combining Pb and Nd isotopic tracers with the Os data, we demonstrate that the low-Ti basaltic magmas in the Emeishan CFB were mainly sourced from a mantle plume reservoir, whereas the high-Ti basaltic magmas were most likely derived from a SCLM reservoir or were contaminated by a significant amount of lithospheric mantle material during plume-related magma ascent through the SCLM. © 2007 Elsevier Ltd. All rights reserved.
Keywords: Permian; Paleozoic::Permian; Палеозой::Пермская